Quelques procédés à ancrer dans le système financier mondial - Abdenour, Touati (Sciences humaines; Vol. 27 (2012): SCIENCES HUMAINES)
بعض الآليات المصرفية التي من شأنها تدعيم المنظومة المالية الدولية   المقال يتطرق إلى ضرورة إقحام بعض الآليات المصرفية التي من شأنها تدعيم المنظومة المالية الدولية، ولا سيما على مستوى البلدان النامية. في هذا السياق، فإننا  نثير ثلاث ظواهر "تَمْليكِية" –تعبير جديد  مشتق من كلمة المِلكية - بحيث إن بقي النظر إليها من الزاوية الحالية، فمما لا شك فيه أنها تواصل في حرمان المنظومة النقدية الدولية من تدفقات مالية معتبرة، و على نقيض ذلك إذا تغيرت نظرة القائمون على شؤون المنظومات النقدية الوطنية و المنظومة المالية العالمية وفق التوجهات المتبناة في مقال الحال  فإنها قادرة على تدعيم جهود تعبئة الموارد المالية على الصعيد المحلي والدولي، وهي : -أولا عملية الحد أو القضاء على ظاهرة ما يعرف بالأملاك المشابهة للأملاك الوقفية آي، أنها تعني أساسا الملكية العقارية، الطرح  الثاني يتطرق إلى ضرورة الحد من خطر الإكتناز لأسباب دينية و التي تنتشر بالخصوص في مجتمعات العالم الإسلامي.إذن الشق الأول والثاني يتعلق بالملكية الفردية العقارية أو النقدية،  أما العملية الثالثة والأخيرة فهي مرتبطة بالصناديق المالية السيادية، بحيث يستوجب تبني نظرة وسطية معتدلة حيالها، لكونها مهددة بالاكتناز بسبب السياسات الحمائية التي تتعرض لها من قبل سلطات بعض الدول المتقدمة المستقبلة لهذا النوع من رؤوس الأموال.      Anchoring some processes in the global financial system     This article discusses the need to engage some of the banking mechanisms able to strengthen the international financial system, particularly in developing countries. Indeed, under this approach, we raise three phenomena capitalization - so that if the promoters of international financial management persist in their current vision is no doubt that they continue to deny the international monetary system of large flows financial and otherwise, but in case of change of vision along the lines adopted in this article it is quite possible to enhance the mobilization of financial resources locally and internationally. In this context, we raise three processes, which are able to take full advantage of the efforts to mobilize financial resources, the first being the reduction process, properties similar to the goods in mortmain, the second , is made on the curb hoarding religious vocation is a phenomenon which characterizes the Islamic world, so the first and the second processes deal with property and assets belonging to individuals, however, the third and final process is related to sovereign funds or those considered as such, who are at risk of forced hoarding. So that the international financial managers should take a moderate view because sovereign funds are threatened by protectionist policies of some developed countries who receive this category of capital.